Judges' Legal Reasoning at the Bengkayang Religious Court in Granting Petitions for the Marriage Dispensation of Minors Under Law Number 16 of 2019 - Rahel Dwi Maharani; Dzulkifli Al’Amin; Andi Muh. Taqiyuddin BN; Ahmad Nuh (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to examine the legal reasoning of judges at the Bengkayang Religious Court in granting petitions for the marriage dispensation of minors. Marriage dispensation is a concession granted by the court to prospective spouses who have not reached the minimum marriageable age of 19 years, as regulated under Law Number 16 of 2019. In deciding a marriage dispensation petition, judges do not rely solely on juridical aspects but are also obliged to consider the facts established through evidence as well as the needs of the petitioners, with the prevention of harm as the primary consideration. This study employs an empirical juridical method with a qualitative approach. The data sources consist of primary data in the form of interviews with judges and the Bengkayang Religious Court Decree Number 5/Pdt.P/2026/PA.Bky, as well as secondary data in the form of legislation, books, and legal journals. The findings show that, in deciding petitions for the marriage dispensation of minors, the Bengkayang Religious Court relies on the prevailing legal foundations and applies specific considerations adapted to the facts and conditions of the petitioners, so that decisions—whether granted or rejected—aim to eliminate harm to the parties. This study also highlights the norms governing marriage dispensation within the family law system in Indonesia and assesses the consistency of their application from the filing of the petition to the judge's decision.